Discovery of a thin stellar stream in the SLAMS survey. Issue 4 (18th August 2018) - Jethwa, P; Torrealba, G; Navarrete, C; Carballo-Bello, J A; de Boer, T; Erkal, D; Koposov, S E; Duffau, S; Geisler, D; Catelan, M; Belokurov, V
ABSTRACT: We report the discovery of a thin stellar stream – which we name the Jet stream – crossing the constellations of Hydra and Pyxis. The discovery was made in data from the Search for the Leading Arm of Magellanic Satellites (SLAMS) survey, which comprises deep g and r imaging for a 650 deg 2 region above the Galactic disc performed by the CTIO Blanco + DECam. SLAMS photometric catalogues have been made publicly available. The stream is approximately 0.18 deg wide and 10 deg long, though it is truncated by the survey footprint. Its colour–magnitude diagram is consistent with an old, metal-poor stellar population at a heliocentric distance of approximately 29 kpc. We corroborate this measurement by identifying a spatially coincident overdensity of likely blue horizontal branch stars at the same distance. There is no obvious candidate for a surviving stream progenitor.